2002
DOI: 10.1159/000065076
|View full text |Cite
|
Sign up to set email alerts
|

Common C677T Polymorphism of the Methylenetetrahydrofolate Reductase Gene and the Risk of Venous Thromboembolism: Meta-Analysis of 31 Studies

Abstract: Background: Although the common 677 C → T polymorphism of the methylenetetrahydrofolate reductase (MTHFR) gene is implicated in the development of hyperhomocysteinemia, its correlation with venous thromboembolism (VTE) remains controversial. We conducted a meta-analysis of previously published studies to clarify the role of the MTHFR 677 TT homozygous genotype in association with VTE. Methods and Results: Relevant articles were retrieved from a systematic search of Medline and Embase from 1990 to September 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
57
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(63 citation statements)
references
References 28 publications
2
57
0
4
Order By: Relevance
“…The prevalence in Southeastern Europe countries are 45%, 43%, 40%, in Hungary, Ukraine, Russia, respectively (5,26). Although a study performed in Germany showed a 2.12 increased risk of DVT for individuals with the heterozygous genotype, found in 43.8% of patients, the majority of studies showed no association with VTE, concordant with our results (33,(35)(36)(37)(38)(39)(40).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The prevalence in Southeastern Europe countries are 45%, 43%, 40%, in Hungary, Ukraine, Russia, respectively (5,26). Although a study performed in Germany showed a 2.12 increased risk of DVT for individuals with the heterozygous genotype, found in 43.8% of patients, the majority of studies showed no association with VTE, concordant with our results (33,(35)(36)(37)(38)(39)(40).…”
Section: Discussionsupporting
confidence: 90%
“…26 (24,29,33,35,36) and a 20% increased risk of VTE (37), whereas other studies failed to reveal any significant association (25,(38)(39)(40). Previous Romanian studies regarding thrombophilia in obstetric cases detected frequencies of the homozygous MTHFR 677TT genotype of 19.4% and 19.56% in pregnant patients with haemorrhagic complications and in patients with repetitive spontaneous abortions; no significant associations were found, except for a slightly increased risk for repetitive abortions in the presence of this genotype (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…An MTHFR 677TT genotype was not significantly associated with VTE (OR, 1.13; 95% CI, 0.70-1.81). Ray et al (28) reported that the classic MTHFR C677T gene polymorphism is weakly associated with an increased risk of VTE. It is unlikely that the purported correlation between hyperhomocysteinemia and VTE is mediated by this gene defect to a substantial degree, although other unidentified gene polymorphisms may explain this association.…”
Section: Discussionmentioning
confidence: 99%
“…These patients are considered milder homozygotes/ heterozygotes for cystathione beta synthase or methylene tetrahydrofolatereductase (MTHFR) deficiency. 6,7 It has been found that homozygous MTHFR mutation is associated with various complications in pregnancy like preeclampsia, placental abruption, but whether recurrent pregnancy loss is associated or not, yet to be proved. 7 Though prospective randomized controlled trial of lowering serum homocysteine levels with supplements of folic acid, vitamin B 6 & vitamin B 12 against a placebo over a 5 year period in patients with vascular disease or diabetes have not however shown any reduction in major cardiovascular events, 8 meta analysis has suggested that folic acid supplementation reduces the risk of stroke by 18%.…”
Section: Discussionmentioning
confidence: 99%